Peran Orang Tua dalam Mengoptimalkan Kecerdasan serta Kehidupan Spiritual Anak Menurut Amsal 1:7 - Udam, Geissler; Baskoro, Paulus Kunto (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: The role of parents is very important in a child growth perioed, both spiritually and physically. Often Christian families are not serious about educating their children. Currently, many families focus more on work and ignore their children’s education. Children’ education is handed overe to household assistants of children grow up on their own without God’s direction. In fact, the role of parents is very important fos children’s spiritual growth, especially in children’s intelligence and maturity. Because children are the successors of the family, church and nation. Educational attiention to children is very important. The author uses the basis of the Book of Proverbs as part of examining the role of parents in educating children. This research was conducted using descriptive qualitative methods. Namely research that focuses on exploring data from library soutces. The aim of this research is First, to explain how important the role of parent is in children’s education. Second, examine the role of parents in educating children according to The Book of Proverbs. Third, implementing the role of parents for today’s children in optimizing children’s intelligence and spiritual life. Abstrak: Peranan orang tua sangatlah penting dalam masa pertumbuhan seorang anak, baik dalam pertumbuhan secara rohani dan jasmani. Seringkali keluarga Kristen tidak serius dalam mendidik anak mereka. Saat ini banyak keluarga lebih befokus kepada pekerjaan dan mengabaikan pendidikan anak. Pendidikan anak diserahkan kepada asisten rumah tangga atau anak-anak bertumbuh sendiri tanpa arahan orang Tuhan. Padahal peran orang tua, sangat penting bagi pertumbuhan kerohanian anak, terutama dalam kecerdasan dan kedewasaan anak. Sebab anak adalah penerus keluarga, gereja dan bangsa. Perhatian pendidikan kepada anak sangat penting. Penulis menggunakan dasar Kitab Amsal sebagai bagian mengkaji peranan orang tua dalam mendidik anak. Penelitian ini dilakukan dengan metode kualitatif deskritif. Yaitu penelitian yang berfokus menggali data dari sumber-sumber pustaka. Tujuan dari penelitian ini adalah Pertama, menjelaskan betapa penting peranan orang tua dalam pendidikan anak. Kedua, mengkaji peranan orang tua dalam mendidik anak menurut Kitab Amsal. Ketiga, mengimplementasikan peranan orang tua bagi anak-anak masa kini dalam mengoptimalkan kecerdasan dan kehidupan spiritual anak.